Addressing the Conflict between Mobility and Stability in Oxide Thin‐film Transistors - Lingyan Liang; Hengbo Zhang; Ting Li; Wanfa Li; Junhua Gao; Hongliang Zhang; Min Guo; Shangpeng Gao; Zirui He; Fengjuan Liu; Ce Ning; Hongtao Cao; et al. (Advanced Science)
Abstract Amorphous oxide semiconductor thin‐film transistors (AOS TFTs) are ever‐increasingly utilized in displays. However, to bring high mobility and excellent stability together is a daunting challenge. Here, the carrier transport/relaxation bilayer stacked AOS TFTs are investigated to solve the mobility‐stability conflict. The charge transport layer (CTL) is made of amorphous In‐rich InSnZnO, which favors big average effective coordination number for all cations and more edge‐shared structures for better charge transport. Praseodymium‐doped InSnZnO is used as the charge relaxation layer (CRL), which substantially shortens the photoelectron lifetime as revealed by femtosecond transient absorption spectroscopy. The CTL and CRL with the thickness suitable for industrial production respectively afford minute potential barrier fluctuation for charge transport and fast relaxation for photo‐generated carriers, resulting in transistors with an ultrahigh mobility (75.5 cm2 V−1 s−1) and small negative‐bias‐illumination‐stress/positive‐bias‐temperature‐stress voltage shifts (−1.64/0.76 V). The design concept provides a promising route to address the mobility‐stability conflict for high‐end displays.